P19 A simtech instant messaging group – quality support at your fingertips. (5th November 2017) - Gay, Christopher
Abstract : Background: There are several forums and online groups for Simulation Technicians, yet the format of many of these means that instant access and reply is not easily achieved. Due to the ever expanding knowledge Simulation Technicians are expected to have, they often need fast reliable support with a technical issue at short notice. The idea of an instant messaging group has been discussed several times, but as yet opportunity to set one up with a critical mass of enough technicians to make it useful has not been possible. Project Description: During the first (ASPIH North SimTech Day1) in Sunderland 12 technicians attended from the Yorkshire and North East localities. Due to the number of new in post technicians present it was discussed that peer support was essential, so it was decided to start the group. The messaging application WhatsApp was chosen as it was freely available cross platform and had features such as encryption, picture sharing and group options. Outcomes: The group initially had 12 members from the North SimTech1 day, then as subsequent events happened (South Simtech Day2, YHSCN Tech Day3) the number grew to 26 as of May 2017. The group sees activity on most days, and has led to on demand support being given, such as- * Urgent assistance being provided on insitu simulation using SMOTS camera equipment * Sharing of Simulation planning templates * Sharing of relevant training opportunities that would've otherwise been missed * Sharing advice on setup of Simulation vehicle * Simulation manikin lifespan discussion * Academic support with submission of abstracts Conclusions: As the group grows the knowledge and experience base increases with it, becoming more useful. Several members have commented about increase in working moral knowing they have a peer support network so easily reachable where non existed before. There may be potential for the group to become too large leading to missing key information, but this will be managed as and when it happens. References: . Simtech North ASPIH Event, 26th Jan 2017. . Simtech South ASPIH Event, 24th March 2017. . YHCSN Regional Meeting, Hull, 25th April 2017.